'Come out and live on your land again': sovereignty, borders and the Unist'ot'en camp. (14th May 2019) - Midzain-Gobin, Liam
Borders are often understood as 'tools' of sovereign power and as establishing the very possibility for authority in the international system of sovereign states (Salter, 2012). This paper seeks to problematise this perspective by looking at the case of the Unist'ot'en Action Camp in northern British Columbia, which has engaged bordering practices including having established a checkpoint on the roadway into the Unist'ot'en territory and actively policing helicopter traffic into the territory. Looking at the Camp, this paper argues that such bordering practices draw upon traditional Indigenous ways of being in order to contest and undo settler sovereign authority, in contrast to the traditional understanding of borders as working to organise settler authority. Understood this way, the paper argues that when inscribed with Indigenous knowledge and when relying on Indigenous authorities, borders and bordering practices can be read as gateways to 'meaningful decolonisation.'